Theory Continuance Technology (TCT): Exploring The Effect of Self-Efficacy As Antecedent And Satisfaction On Continuance Intention Of Gas Station Self-Service Technology - Andreatea Ottemusu, Maria; Adeline, Michelle; Chandra, Sylvia; Anggraeni, Adilla (Journal of World Science, 2023)
This research aims to assess the intention to use SST by customers at Jabodetabek gas stations. To investigate the influence of customer self-efficacy on SST continuance intention at gas stations. To determine the effect of satisfaction on SST continuance intention at gas stations. Moreover, to assess customer satisfaction and continuance intention after using SST at gas stations. The method used in this research is quantitative; data analysis techniques are used to conduct statistical tests consisting of convergent validity tests, discriminant validity tests and reliability tests. So, the results of this research show that providing more accurate and precise information in the post-COVID pandemic period, especially in the self-efficacy section. In this study, we expand the Continuance Technology Theory (TCT) by adding self-efficacy as an antecedent. This research has implications for companies that should listen to customer input, increase interaction, and strengthen self-efficacy. This research provides an important basis for implementing kiosks in the gas station industry.